O atual processo de decadência da vida de bairro em Olaria à luz do estudo de suas diversas espacialidades - Sampaio, Jorge Armando (2009)
The objective of this essay is the study of the causes of the current decadence of the life of Olaria district, through the identification of the various spatiality that exist there. The theoretical and methodological basis of this study is based on work written by the philosopher Henri Lefèvbre, that, among many contributions, developed the method progressive-regressive and he defended the need to study the district based on the concept of totality, to promote the overcome what is classified as "ideology of the district." The identification of several spatiality of Olaria demanded the study of the process of socio spatial from the period when it was still a part of the old Parish of Inhaúma to the present day. During this retreat in history, were taken into account events of various scales that had some influence in this process. The search for empirical data occurred, especially by carrying out work in the field, observation of daily of Olaria, taking photographs, maps, production, application of questionnaires and conducting interviews with residents of the district. The results achieved allow testify that the current spatiality that exist in Olaria does not contribute to the meeting and the strengthening of district relations among its residents, in contrast, the possibility of an effective life of the district, are seriously compromised. This fact is easily understood by a term widely used by the residents of Olaria - "the other side of the district" - which symbolizes the existence of two "sides" unequal in the district due to the passage of the Leopoldina Railway. Some factors can be indicated as the main causes of the decay of life of the district: the changing role of the Leopoldina Railway because of the valorization of the road transport rather than rail, the process of expansion the metropolis, an increase of impersonal relations in the contemporary world and the great increase of the violence. The spatiality of Olaria, which until the early 1980´s itself was that of a district, now appears to be equivalent to a portion immersed in the metropolis